1954
DOI: 10.3181/00379727-85-20782
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Study of Hydrocortisone in Rats

Abstract: 1case the peak is reached a t the polychromatic stage (94%), and higher activity is revealed in the basophilic erythroblasts. These data should be considered in relation to relatively earlier sampling (3 hours), the higher radioiron dosage (100 pc), and the stimulation of bone marrow by previous bleeding.The present investigation then shows that in the rat and with the doses used, there is a definite turnover of radioiron even by the earliest erythroid elements, namely proerythroblasts and basophilic erythrobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1955
1955
1965
1965

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Bradlow, Dobriner and Gallagher (10) found that 70 per cent of a dose of tritium-labeled cortisone administered to mice was found in the liver within five minutes after intravenous administration. Administered cortisol also disappears rapidly from the circulation in rats (11), and this rapid metabolism can be prevented by hepatectomy but not by nephrectomy (12).…”
mentioning
confidence: 99%
“…Bradlow, Dobriner and Gallagher (10) found that 70 per cent of a dose of tritium-labeled cortisone administered to mice was found in the liver within five minutes after intravenous administration. Administered cortisol also disappears rapidly from the circulation in rats (11), and this rapid metabolism can be prevented by hepatectomy but not by nephrectomy (12).…”
mentioning
confidence: 99%
“…In any case, the present data show that calculation of a single theoretical volume of distribution, v, is unwarranted since it is based on the assumption that the concentration of cortisol is the same throughout the entire volume of distribution as it is in the plasma. Since v proves to be larger than the total body volume both in these experiments and in those of others (6,10), the concentration of cortisol in sites of binding outside of the plasma appears to be much higher than in the plasma.…”
Section: Methodsmentioning
confidence: 88%
“…At a later Kelley (4) found that the half-life of 17-hydroxy- (6) found a half-life in 20 normal subjects of 114 ± 6.5 minutes, with a range of 90 to 130 minutes. This constant rate is due mainly to the activity of the liver, since Tomizawa, Narahara, Gibbons, and Williams (10) showed that hepatectomized rats did not metabolize cortisol, and Brown, Willardson, Samuels, and Tyler (3) found that in patients with liver disease the disappearance rate of 17-hydroxycorticosteroids was slowed proportional to the retention of bromosulfaphthalein. Peterson, Wyngaarden, Guerra, Brodie, and Bunim (6) also found increased half-lives in all their patients with liver disease.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of such conversions on the over-all rate of disappearance of hydrocortisone from the body fluids may be masked by the strictly degradative processes. Both in vivo (8,11,12) and in vitro (13)(14)(15) experiments indicate that the liver plays a major role in the disappearance of hydrocortisone from the blood. That the chemical transformations in the liver are not essential for the biological activity of hydrocortisone is suggested by the fact that this steroid can exhibit its metabolic actions in the hepatectomized animal (16).…”
Section: Commentmentioning
confidence: 99%